Highly sensitive detection of Staphylococcus aureus by a THz metamaterial biosensor based on gold nanoparticles and rolling circle amplification. Issue 45 (17th July 2020) - Yang, Ke; Yu, Wenjing; Huang, Guorong; Zhou, Jie; Yang, Xiang; Fu, Weiling
Abstract : A highly sensitive method for detecting Staphylococcus aureus ( S. aureus ) is urgently needed to reduce the impact and spread of hospital-acquired infections and food-borne illness. Abstract : A highly sensitive method for detecting Staphylococcus aureus ( S. aureus ) is urgently needed to reduce the impact and spread of hospital-acquired infections and food-borne illness. For this purpose, this paper presents a THz metamaterial biosensor based on gold nanoparticles (AuNPs) and rolling circle amplification (RCA). The RCA process amplified the S. aureus DNA fragments and generated copious yields of long single-strand DNA molecules. These molecules were then conjugated with the AuNPs to form complexes that delivered exceptional increases in the refractive indices of the samples, and resulted in corresponding improvements in the THz response of the metamaterial. Under optimal conditions, the shifts in the metamaterial's resonance frequency displayed a linear relationship with concentrations of synthetic S. aureus DNA in the range from 10 fM to 10 pM, with a limit of detection of 2.77 fM. We also tested the practical application of this biosensor in measurements of genomic DNA in clinical bacterial strains, where the sensor showed a detection limit of 0.08 pg μL −1 and a linear range from 0.1 to 5 pg μL −1 . It also exhibited reasonable specificity, resisting interference from three other pathogenic bacteria. These findings indicate that the proposed approach offers a cost-effective THz biosensing strategy that can be easily fabricated and conveniently operated to aid the diagnosis of infectious disease and food safety control.